Measuring the invisible: A key performance indicator for managing construction logistics performance. Issue 6 (6th August 2018) - Ying, Fei; Tookey, John; Seadon, Jeff
Abstract : Purpose: Construction logistics is an essential part of Construction Supply Chain Management for both project management and cost aspects. The quantum of money that is embodied in the transportation of materials to site could be 39–58 per cent of total logistics costs and between 4 and 10 per cent of the product selling price for many firms. However, limited attention has been paid to measure the logistics performance at the operational level in the construction industry. The purpose of this paper is to contribute to the knowledge about managing logistics costs by setting a key performance indicator (KPI) based on the number of vehicle movements to the construction site. Design/methodology/approach: A case study approach was adopted with on-site observations and interviews. Observations were performed from the start of construction until "hand-over" to the building owner. A selection of construction suppliers and subcontractors involved in the studied project were interviewed. Findings: Data analysis of vehicle movements suggested that construction transportation costs can be monitored and managed. The identified number of vehicle movements as a KPI offers a significant step towards logistics performance management in construction projects. Originality/value: This research paper demonstrates that framework of using vehicular movements meet the criterion of effective KPI and is able to detect rooms for improvements. The key findings shed valuable insight for industry practitioners in initiating the measurement and monitor "the invisible logistics costs and performance". It provides a basis for benchmarking that enables comparison, learning and improvement and thereby continuous enhancement of best practice at the operational level, which may accelerate the slow SCM implementation in the construction industry.